A Life-Centered Approach to Bioethics : Biocentric Ethics / [electronic resource] - Johnson, Lawrence E. (Cambridge : Cambridge University Press, 2010)
Approaches bioethics on the basis of a conception of life and what is needed for the affirmation of its quality in the most encompassing sense. Johnson applies this conception to discussions of controversial issues in bioethics including euthanasia, abortion, cloning and genetic engineering. His emphasis is not on providing definitive solutions to all bioethical issues but on developing an approach to coping with them that can also help us deal with new issues as they emerge. The foundation of this discussion is an extensive examination of the nature of the self and its good and of various approaches to ethics. His bioethic is integrally related to his well-known work on environmental philosophy. The book also applies these principles on an individual level, offering a user-friendly discussion of how to deal with ethical slippery slopes and how and where to draw the line when dealing with difficult questions of bioethics.
Title from publisher's bibliographic system (viewed on 09 Oct 2015).
Keywords: Bioethics